2013
DOI: 10.1084/jem.20130275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bone morphogenetic protein 7 (BMP7) as an instructive factor for human epidermal Langerhans cell differentiation

Abstract: Bone morphogenetic protein 7 (BMP7) promotes the differentiation of Langerhans cells in the epidermis during prenatal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 61 publications
7
89
2
1
Order By: Relevance
“…3B). These results confirmed that BMP-7 can readily replace TGF-b1 to induce langerin high LC-like cells as proposed by others (40). We additionally reported no additive or synergistic effect of those factors when put together on differentiating cells (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…3B). These results confirmed that BMP-7 can readily replace TGF-b1 to induce langerin high LC-like cells as proposed by others (40). We additionally reported no additive or synergistic effect of those factors when put together on differentiating cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In line with this, sparse studies reported basal GM-CSF synthesis in human and murine skin or colonic mucosa, most predominantly by KCs and fibroblasts (66)(67)(68). Interestingly, Yasmin et al (40) have clearly shown that BMP-7 precedes TGF-b1 during embryonic life, between 8-10 and 9-11 wk estimated gestational age, respectively (69). Both cytokines are still expressed in adult skin basally and suprabasally, respectively (40).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…BMP7 signaling was reported to play a critical role in LC development (11). A recent study (13) (14) recently reported that Irf8 expression leads to an increase in Id2 transcript levels.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-b promotes the development of DCs, and TGF-b-null mice have a defect in the development of epidermal Langerhans cells (LCs) (9,10). A recent study (11) identified another TGF-b superfamily ligand, BMP7, as an instructive factor for human epidermal LCs. TGF-b1 was reported to upregulate Irf8 during DC development (12).…”
mentioning
confidence: 99%